Extra-Anatomical Bypass: A Surgical Option for Recurrent Aortic Coarctation - Alban Malaj; Ombretta Martinelli; Francesco Giosue' Irace; Jihad Jabbour; Bruno Gossetti; Giuseppe Mazzesi (Case Reports in Vascular Medicine)
Background. Balloon aortoplasty with or without stenting is a less invasive alternative to open surgery for the management of recurrent isthmic coarctation. However, in patients with previous small size tube graft, an open surgical correction is mandatory and, in most cases, an anatomical aortic reconstruction is carried out. Methods. We present the case of a 48-year-old woman with recurrent aortic coarctation and systemic hypertension with systolic value around 190–200 mmHg and preoperative systolic pressure gradient 70 mmHg, submitted to an extra-anatomical bypass. Through a median sternotomy, an extra-anatomical bypass from ascending to descending aorta was performed. Results. No intra- or postoperative complications were observed. The postoperative pressure gradient was 10 mmHg and the systolic pressure ranged from 130 to 140 mmHg. Conclusion. The extra-anatomical bypass can be considered an effective and safe alternative to the anatomical aortic reconstruction in the cases with recurrent aortic coarctation unfit for endovascular treatment.